Differences between men's and women's performance in swimming - Sambanis, M.; Kofotolis, N.; Sambanis, P. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
In the events where the participation of the aerobic system of energy production was bigger, that is in long distances (800-1500 m) and middle distances (200-400 m), the women showed the smallest differences in the records compared to men swimmers. On the contrary in the events of speed which required more strength the differences were larger